Effect of Cu and SiO₂ on a Remelted-Recycled Piston Alloy Under Vertical Centrifugal Casting Conditions - Triyono, Teguh; Surojo, Eko; Prabowo, Aditya Rio; Triyono, Triyono; Djordjevic, Branislav; Carvalho, Hermes; Adie, Prayoga Wira; Sholehuddin, Muhammad Ilham (Civil Engineering Journal, 2026)
Functionally graded aluminum matrices produced by means of centrifugal casting offer a route to location-specific properties, yet sustainable feedstocks and dual-density reinforcements are less well explored. In this work, we evaluate vertical centrifugal casting (VCC) of a remelted, recycled piston alloy reinforced with silica (SiO₂) and copper (Cu) particulates selected for their contrasting densities relative to the matrix. Castings were produced at 1000 rpm for 5 minutes using a 500 °C preheated mold and an 800 °C pour temperature. Cu was added at 1–4 wt.% and SiO₂ was added at 0–9 wt.%. Bulk density/porosity measurements, Vickers hardness testing, and optical/SEM microstructural analysis were employed to characterize the resulting gradients. The density increased with the radial distance from the rotation axis, accompanied by a monotonic decrease in porosity, consistent with centrifugal separation. Microstructurally, SiO₂ concentrated toward the inner region near the rotation center; in comparison, Cu was enriched at the outer periphery. Correspondingly, hardness exhibited a spatial gradient: SiO₂-reinforced zones were hardest near the inner region, whereas Cu-rich outer zones were hardest at the external rim. These results demonstrate that VCC of a recycled Al–Si feedstock can be used to reliably tailor its microstructure and properties through density-driven particle segregation, enabling controllable, bidirectional functional grading using environmentally friendly starting materials.